Scorched (2011)
Colour Ted Quinlan (producer), Clar Doyle (director), Darrel Brenton (associate director), Jennifer Nakashima (stage manager), Jim Hoskins (set design), Carol Wadden (costume design), George Robertson (sound design), Dawn Mason (property master), Beothuck Street Players